Review: Implications of Air Pollution on Trees Located in Urban Areas - Alamilla-Martínez Diana Grecia; Tenorio-Sánchez Sergio Arturo; Gómez-Ramírez Marlenne (Earth)
Air pollution in cities is intensifying, inevitably affecting all living organisms, gincluding trees. Urban trees are vital for cities because they improve air quality and regulate the climate; however, like all living organisms, they are affected by the environment to which they are exposed. In cities, the primary atmospheric pollutants of inorganic origin include NO, SOX, COX, O3, and suspended particulate matter (PM2.5 and PM10). Each of these pollutants impacts population health, with urban trees undergoing a series of consequent alterations. In this study, we review the inorganic pollutants identified by the World Health Organization (WHO) as impacting air quality in cities in different regions of the world; discuss the regulations that govern NO2, SO2, CO, O3, and PM2.5 and PM10 emissions and their impact they have on urban trees; analyze the processes involved in pollutant–tree interactions and the related tolerance and/or resistance mechanisms; and determine the tree species with the best tolerance, classified using an air pollution tolerance index (APTI).